Model for a new sylvo-pastoral system in the Mamora cork-oak forest - Montoya Oliver, Jose Miguel (Landscape and Urban Planning, 1986)
The Mamora cork forest (central Morocco), located on sandy soils in the Moroccan coastal plain where the climate is semiarid (annual rainfall, depending on the zone, in the range 400–600 mm) with very dry summers and temperate-warm winters, covers 60 000 ha and is the largest cork forest in the world. The trees in this forest are vital in that they protect and improve the pasture growing beneath them, as well as producing abundant fruit that can be eaten by livestock, and foliage which can serve as emergency feed. This, combined with its special geographic/regional location, makes Mamora an important pasturing area. It also produces some 40% of Moroccan cork and is therefore of great sylvicultural and industrial significance also, making it a sylvo-pastoral area of major economic and social importance at both regional and national levels.
Keywords: activité forestière; écologie; élevage; emploi; forêt; prairie; PVD (citation); utilisation du sol